THE INFLUENCE OF DIGITAL LITERACY, LEARNING DISCIPLINE, AND SELF-ESTEEM ON THE WORK READINESS - Dianti, Tania Rahma; Zulaihati, Sri; Swaramarinda, Darma Rika (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to determine the effect of digital literacy on work readiness, the effect of learning discipline on work readiness, the effect of self-esteem on work readiness, and the effect of digital literacy, learning discipline, and self-esteem on work readiness collectively. The method used in this study was quantitative with a purposive sampling technique. The population and sample used in this study were all undergraduate students, totaling 272 respondents, with data collected through a questionnaire survey. Digital literacy, learning discipline, self-esteem, and work readiness were measured using a Likert scale. Data analysis in this study used SPSS software version 25. The results of the study indicate that the influence of digital literacy on work readiness is positive and significant. The influence of learning discipline on work readiness is positive and significant. The influence of self-esteem on work readiness is positive and significant. The influence of digital literacy, learning discipline, and self-esteem on work readiness is positive and significant. Therefore, by improving digital literacy and academic discipline, as well as building positive self-esteem, individuals can be better prepared to face challenges in the workplace.